Forest Diversity and Carbon Sequestration In Resunga Sacred Grove, Gulmi, Nepal - Sharma, Bhuvan Keshar; Pokharel, Chandra Prasad; Shrestha, Laxmi (Journal of Natural History Museum, 2018)
Resunga forest is a store-house of diverse wildlife and wild plants ranging from sub-tropical to temperate climatic zones in the midhill physiographic region. Aiming to assess the forest diversity and sequestrated carbon, this study was conducted in Resunga religious forest. Data were collected from systematically distributed plots at the interval of 50m elevation along the altitudinal gradients from 2100–2450 m elevation. Eight circular plots of 10 m radius were used to collect information on tree level characteristics. Importance value index, Shannon-Weiner index of diversity and evenness were used to assess the forest diversity. Published allometric functions were used to examine the aboveground tree biomass. Tree carbon stocks were calculated using carbon fraction value. Nineteen tree species were recorded from Rhododendron and oak forests. Comparing the forest types, Rhododendron forest was more diverse (H = 1.0) than oak forest (H = 0.9). Similarly, tree species were more evenly distributed (0.87) in the oak forest than that of Rhododendron forest (0.77). The vegetation carbon stock of Rhododendron forest was lower (101.8 t/ha) than that of oak forest (153.8 t/ha). Overall, the average vegetation carbon stocks in the Resunga Sacred Grove (RSG) was 127.75 t/ha. J. Nat. Hist. Mus. Vol. 29, 2015, Page: 60-69